1980
DOI: 10.1007/bf00431264
|View full text |Cite
|
Sign up to set email alerts
|

Platelet uptake of serotonin in psychotic children

Abstract: Platelet serotonin (5-HT) uptake was assayed in ten long-term hospitalized children subdivided into two diagnostic groups "autistic" and "other psychotic". Weekly blood samples were taken from these children over a period of 6-7 weeks and serotonin uptake was determined. Constant and significant uptake values (13.28 +/- 2.0 pmol serotonin/10(8) platelets/5 min for autistics and 9.59 +/- 1.58 pmol serotonin/10(8) platelets/5 min for other psychotics) were obtained. There was no correlation with drug treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In addition, it is possible that enhanced 5-HT accumulation in platelets is responsible for the reduced PPP 5-HT level. This is supported by several studies [24][25][26], but not all [27], which have demonstrated increased 5-HT platelet uptake in autism. While speculative, this may be subsequently associated with increased platelet 5-HT levels and parallel diminished 'free' plasma 5-HT levels.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, it is possible that enhanced 5-HT accumulation in platelets is responsible for the reduced PPP 5-HT level. This is supported by several studies [24][25][26], but not all [27], which have demonstrated increased 5-HT platelet uptake in autism. While speculative, this may be subsequently associated with increased platelet 5-HT levels and parallel diminished 'free' plasma 5-HT levels.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, further studies provided evidence that blood 5-HT level is a highly heritable trait (Leventhal et al, 1990 ; Weiss et al, 2005 ; Muller et al, 2016 ), indicating that the changes found in hyperserotonemic ASD subjects may have identifiable genetic determinants. Because platelets do not synthesize 5-HT but acquire it from the bloodstream via SERT, and because a single gene expresses SERT found in both the brain and platelets (Lesch et al, 1993 ; Ramamoorthy et al, 1993 ) the transporter has been a major focus for models seeking to connect hyperserotonemia to ASD (Rotman et al, 1980 ; Piven et al, 1991 ; Cook and Leventhal, 1996 ).…”
Section: Introduction: Serotonergic Connections To Asdmentioning
confidence: 99%